Low-Cost Surface Passivation For Black Silicon Solar Cells By Liquid Phase Deposition Techniques - Ahmad, Sheriff Muhiddin (2023)
Black silicon (b-Si) is a promising surface structure for solar cells due to its low broadband reflectance and superior light trapping properties within the 300–1100 nm wavelength region. For the fabrication of b-Si, one-step electroless metal-assisted chemical etching (MACE) is employed which produces nanowires (NWs) with heights of about 0.4 – 0.8 μm that result in low broadband reflectance but leads to high surface recombination in b-Si solar cells. To address this issue, efficient surface passivation is inevitable, which is essential for developing high-efficiency b-Si solar cells. Surface passivation by the formation of thermal silicon dioxide (SiO2) is the conventional method that involves high-temperature processing. The high process temperatures could deteriorate the nanotextured b-Si formed by the etching process, compromising broadband light absorption in the solar cells. Therefore, liquid phase deposition (LPD) is a promising alternative surface passivation technique that can reduce the surface recombination issue.